Teacher self-efficacy: a second-order confirmatory factor analysis of student engagement, instructional strategies, and classroom management among secondary school teachers - Mohd Faiz Mohd Yaakob; Mohammad Ahmad Abdelaziz Al-Zu’bi; Kholoud Imhammad Meqbel Al-Mseidin; Mat Rahimi Yusof; Mohd Sofian Omar Fauzee; Marni Ishak; Ismahany Abdul Rahman (International Journal of Evaluation and Research in Education (IJERE), 2026)
Teacher self-efficacy plays an important role in improving teaching effectiveness and student learning outcomes; however, a validated measurement model tailored to the local educational context remains limited. Therefore, this quantitative study aims to develop a measurement model of teachers’ self-efficacy in Malaysia. The proposed model consists of three dimensions: student engagement (SE), instructional strategies (IS), and classroom management (CM). Data were collected from 144 teachers using a modified questionnaire based on the teacher sense of efficacy scale (TSES). the data were analyzed using confirmatory factor analysis (CFA) through structural equation modeling (SEM) with AMOS. The findings confirmed that 12 suggested behaviors were acceptable within the model. The CFA results demonstrated satisfactory factor loadings (FL) and reliability for SE (FL=0.758–0.820, composite reliability (CR)=0.870, average variance extracted (AVE)=0.627, square root of AVE (√AVE)=0.792), IS (FL=0.696–0.875, CR=0.895, AVE=0.683, √AVE=0.826), and CM (FL=0.741–0.864, CR=0.819, AVE=0.619, √AVE=0.871). These findings indicate that the proposed measurement model demonstrates acceptable validity and reliability and provides a useful framework for evaluating teachers’ self-efficacy and supporting efforts to enhance teaching quality in the Malaysian educational context.